Monitoring training load in sprint interval exercises - Nummela, A. (New Studies in Athletics, 2014)
ABSTRACT Current methods for assessing sprint training such as stopwatch timing and monitoring the athlete's perceived exertion, heart-rate recovery and blood lactate measurements are useful tools, but none provide unambiguous measures of training load. The purpose of this three-part study was to investigate the validity of different training load descriptors, including a new model for measuring training load in sprint interval exercises (SIEs) and over the course of a training period. The author compares data collected from single sprints of various intensities performed on separate days by eight athletes, from SIEs performed over the course of three months by 16 athletes and from the training of a single athlete in two eight-week periods. He concludes that a combination of methods is best for accurately monitoring training load but coaches and athletes should be aware of individual physiological responses, since similar training may not give similar adaptations for each individual. In addition, he finds that the index of sprint training load provided by the new model has certain practical advantages as it is non-invasive and does not require expensive devices yet correlates well to the other measures studied.